The Influence of Body Composition Effects on Male Facial Masculinity and Attractiveness - Lei, Xue; Holzleitner, Iris J.; Perrett, David I. (Frontiers in Psychology, 2019)
Body Mass Index (BMI) and its facial correlates influence a range of perceptions including masculinity and attractiveness. BMI conflates body fat and muscle which are sexually dimorphic because men typically have more muscle but less fat than women. We therefore investigated the influence of facial correlates of body composition (fat mass and muscle mass) on the perception of masculinity in male faces. Women have been found to prefer more masculine looking men when considering short-term relationships compared with long-term relationships. We therefore conducted a second study of heterosexual women’s preferences for facial correlates of fat and muscle mass under long and short relationship contexts. We digitally transformed face shape simulating the effects of raised and lowered levels of body fat or muscle, controlling for each other, height and age. In Study 1, participants rated masculinity of shape-transformed male faces. The face shape correlates of muscle mass profoundly enhanced perceived masculinity but the face shape correlates of fat mass only affected the perception of masculinity in underweight to low normal weight men. In Study 2, we asked two groups of women to optimise male face images (by adjusting the shape correlates of fat and muscle) to most resemble someone they would prefer, either for a short-term sexual relationship or for a long-term relationship. The results were consistent across the two participant groups: women preferred the appearance of male faces associated with a higher muscle mass for short-term compared with long-term relationships. No difference was found in women’s preference for the face shape correlates of fat mass between the two relationship contexts. These findings suggest that the facial correlates of body fat and muscle have distinct impacts on the perception of male masculinity and on women’s preferences. The findings indicate that body composition needs to be taken into consideration in psychological studies involving body weight.